PERILAKU MAHASISWA DI KEDAI KOPI TITIWUNGEN UTARA KOTA MANADO (STUDI KASUS RUMAH KOPI BILLY) - Isbul Said (HOLISTIK, Journal of Social and Culture, 2022)
Indonesians tend to spend their free time socializing, visiting shopping centers, visiting entertainment venues, or relaxing at their favorite Coffee Shops. Coffee shops in Indonesia are synonymous with simple small shops, with a typical menu of tubruk coffee with bread accompaniment. Coffee shops also have the peculiarity and present an environment that triggers active interaction when someone is in it. Like Billy Samrat Coffee House is one of several places that also develop the same type of business in general, the business that was established approximately 40 years old is located in South Titiwungan, Manado City, it is one of the coffee shops that is crowded with visitors. Not a few consumers also come from various circles of work, social status, education and others. The current phenomenon of coffee shops not only survived in the heyday of coffee shops as interaction stalls in building the discourse of every student, now new appearances that began to appear when the development of information technology penetrated in various parts of the world also influenced coffee shops as interaction stalls because the face that began to shift has now been seen in the coffee shop when the majority of students no longer use coffee shops as interaction stalls in testing every argument but coming and coming together just using the Wi-Fi facility as a bridge through interesting games and photos in carving every social media that exists. Keywords : behavior, student, coffee shop